2004
DOI: 10.1097/01.ta.0000149248.02598.9e
|View full text |Cite
|
Sign up to set email alerts
|

Vacuum-Assisted Fascial Closure for Patients With Abdominal Trauma

Abstract: Patients requiring temporary abdominal closure have a significant in-hospital mortality rate of 33%. Delayed primary closure with vacuum assistance was achieved for 71.9% of the surviving patients. Maintaining a negative or total positive fluid balance of less than 20 L before the last attempted fascial closure improves successful closure rates, as seen in 19 of 22 patients (86.4%). The vacuum-assisted closure technique also enabled successful primary closure for two patients with extreme delay (>8 days). Elev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
0
8

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(85 citation statements)
references
References 14 publications
1
76
0
8
Order By: Relevance
“…The review of 18 series with overall 1395 patients managed by OA and V.A.C. revealed a mean rate of EAFs 6.1% (Table 2), (4,8,14,17,19,20,(26)(27)(28)(29)31,32,(36)(37)(38)42,45,47), which is comparable to 7.2% in our series.…”
Section: Discussionsupporting
confidence: 56%
“…The review of 18 series with overall 1395 patients managed by OA and V.A.C. revealed a mean rate of EAFs 6.1% (Table 2), (4,8,14,17,19,20,(26)(27)(28)(29)31,32,(36)(37)(38)42,45,47), which is comparable to 7.2% in our series.…”
Section: Discussionsupporting
confidence: 56%
“…Si bien el packing para el control del sangrado severo en el traumatismo hepático (Pringle) y en otras lesiones abdominales (Halsed) se conocen desde los años 1900 y 1912, respectivamente, el desarrollo y la difusión de la cirugía de control del daño se producen hacia finales de la década del 80 gracias a Stone en Atlanta y, principios de los 90, a Bruch en Houston 17 . Aunque la adaptación del término "control de daño" al campo del trauma puede ser acreditado a Schwab y cols.…”
Section: Cirugía De Control De Dañosunclassified
“…(1983) cuando se llega a esta instancia "ya es tarde" 17 . Evitar la hipotermia, compensar el medio interno (acidosis metabólica) y seguir reponiendo la volemia son los aspectos para componer desde el momento del trauma, hasta su ingreso en la sala de emergencias.…”
Section: ¿Cuáles Son Las Etapas Para Seguir?unclassified
“…After that, the deliberately created ventral hernia is repaired 6-12 mo later. The above situation has been changed considerably with the introduction of vacuum application and biological prosthetic material [1][2][3][4][5] . Until recently, the practice was to discharge patients with an open fascia and partially closed skin.…”
Section: To the Editormentioning
confidence: 99%
“…It is reported that by using vacuum methods, fascial defects are reduced sufficiently to be closed [1][2][3][4] . It is also reported that in cases where closure is inadequate, by using acellular dermis, patients can be sent home without a fascial defect [5] .…”
Section: To the Editormentioning
confidence: 99%